The gut microflora assay in patients with colorectal cancer: in feces or tissue samples? - Rezasoltani, Sama; Dabiri, Hossein; Asadzadeh-Aghdaei, Hamid; Akhavan Sepahi, Abbas; Modarressi, Mohammad Hossein; Nazemalhosseini-Mojarad, Ehsan (Iranian journal of microbiology, 2019)
Gut microbiota is the complex community of microorganisms that live in the digestive tracts of humans and other animals, including insects. The relationship between gut microbiota and human health is mutualistic and altered bacterial composi- tions in fecal and mucosal specimens of colon in patients with cancer compared to healthy subjects were observed. Thereby, studying the gut microbiota, their interactions with the host and their alterations in colorectal cancer (CRC) patients could be helpful to diagnose and treat the disease in earlier stages. In CRC research, the most common samples are feces and tumor tissues. Interestingly, scientists have quite different views regarding gut microbiota composition of feces and tissues. Some believe bacterial populations in feces and mucosa are completely distinct and differ in composition and diversity while some others declare similar variations. Actually, both types of specimens have some advantages and disadvantages in survey of gut microbiota. Fecal samples serve as a noninvasive approach for screening tests while mucosal associated samples are more powerful for identification of bacteria with adenoma and CRC initiation and growth. Here we have discussed the advantages and disadvantages of two type of specimens in CRC investigations and also discussed the similarities and differences of microbial composition between stool and tissue specimens.